DAMPAK TEKNOLOGI ARTIFICIAL INTELLIGENCE PADA PROFESI AKUNTANSI - Alghafiqi, Burhanuddin (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The development of Artificial Intelligence technology has changed the accounting profession. This paper provides a comprehensive overview of the latest developments in Artificial Intelligence, Big Data, Machine Learning used in business practices in the accounting profession worldwide. This paper explores the evolution of the accounting profession following the latest technological developments and assesses the impact of its development in the future. Challenges and opportunities posed by Artificial Intelligence relating to accounting professionals and the process of accounting education. This study uses a normative juridical approach with library studies with secondary data. This paper provides an overview of how accounting educators and professionals respond to these technological developments and provides further discussion on what accounting professions, institutions and graduates should do to face the challenges of change caused by technological developments.